Intellectual Property in Mexican Labor Law - Curiel Sandoval, Verónica Alejandra (2024)
The innovations, creations, or inventions in the literary, artistic, scientific, industrial, commercial and other fields, which arise during the relationship that unites the worker with an employer, are extremely important for the daily life of society; however, although the legal framework applicable to the protection of these novel tangible or intangible assets is broad, when considering the rights that each person has with respect to the project, product, or element developed, when the creation arises in an employment relationship, it is appreciated a precarious and insufficient regulatory environment, since it has practically been left in legal oblivion. It is significant not to omit that the primary purpose of intellectual property law is to protect the legal interests of the creators of original and/or innovative goods or products, while labor law seeks to protect what is conducive to a workeremployer bond. It is important to note that in the present research the mixed method was used for its respective development.